SOSIALISAI WASTING DAN STUNTING UNTUK GENERASI SEHATDI DESA MOJOPAHIT UPTD PUSKESMAS PUNGGUR KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Sadiman Sadiman; Yoga Tri Widjayanti; Sri Lestariningsih (MAJU : Indonesian Journal of Community Empowerment, 2026)
Wasting (acute malnutrition) is a major nutritional problem in Indonesia, with a prevalence of 7.7% in 2022, still above the WHO maximum standard. Wasting is a condition in which a child's weight drops significantly below the standard growth curve or is considered low (thin). This condition can be caused by inadequate food intake or infectious diseases. The impacts of wasting include decreased immunity, an increased risk of illness and even death, and impaired growth and development. This community service activity aims to increase the knowledge of mothers of toddlers regarding wasting and stunting, as well as their prevention. The methods used were outreach and education (counseling) through lectures and discussions. This activity was held in Mojopahit Village, Punggur District, Central Lampung Regency. The target group was mothers of toddlers, with 21 participants. Knowledge assessment was conducted using pre- and post-tests. Educational media used included leaflets and videos, including a video of Tuina massage. The results of the activity showed an increase in mothers' knowledge of wasting and stunting and their prevention. The average pre-test score increased from 72.86 to 87.14, resulting in a 14.28-point increase in knowledge.